Preventive measures in problematic gaming in Asia: a systematic literature review - Mohd Azul Mohamad Salleh; Normah Mustaffa; Zul Imran Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2023)
The rise of problematic gaming (PG) prevalence among the youth is a growing concern globally. PG is a symptom of Gaming Disorder (GD) that has been classified as a mental disorder by the World Health Organization (WHO) in the International Classification of Diseases 11th Revision (ICD-11). Despite the use of Public Service Announcements (PSAs) as a preventive measure in many countries, their effectiveness in increasing the awareness of PG in Asia, particularly in Malaysia is still questionable. The role of PSAs in preventing PG is a topic that deserves closer examination, open to debate and requires a more critical evaluation. The objective of this study is to identify diverse preventive measures employed to prevent PG in Asia, with a specific focus on determining whether PSA has been used or suggested based on empirical support to enhance awareness among Asian youth. A systematic review of the literature between 2015 and 2022 was performed with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, utilizing Scopus, Web of Science, and Google Scholar as the main sources for the search efforts. We systematically analysed 22 PG and GD prevention articles in Asia between 2015 and 2022, which yielded five main themes which were parent and family prevention, clinical practice, self-control, policy and technology restrictions, and school initiatives. Recommendations for future research in this field have been provided to enhance further understanding and effectiveness of PG and GD prevention efforts in Asia.